The Effect of Probiotic Doses Added to Feed on The Growth of White Snapper (Lates calcalifer) - Amanda, Salsabila; Junaidi, Muhammad; Rahmadani, Thoy Batun Citra (Jurnal Biologi Tropis, 2024)
The target output of white snapper (Lates calcarifer) in 2019–2024 is 10,000–14,000 tons, making it a fish type with bright prospects and economic worth for human consumption. Having access to high-quality feed is a primary aspect in promoting fish growth. Fish will grow more when intake they are give them something they can eat well enough. This will allow the fish to use the energy they get from the feed, which calls for the use of probiotics as a supplement. Probiotics are additional food (supplements) derived from living microorganisms that balance the intestinal microbial flora in the digestive tract to provide benefits to the fish that consume them. The type of probiotic commonly used is EM4 (effective microorganism 4). This study aimed to examine the effects of commercial feed supplemented with EM4 probiotics on the growth, feed efficiency, feed conversion ratio, and survival of white snapper (Lates calcarifer). The fish used in the study were white snapper with a size of 8-11 cm and a seed weight of 5±3 g which were maintained for 60 days. Feeding was done by ad satiation. Five treatments and three replications were included in the fully randomized design of this investigation. The statistics that were noted included survival, absolute weight growth, absolute length growth, feed conversion ratio (FCR), feed efficiency (EPP), and amount of feed consumed. The effects of the EM4 probiotic dose on absolute weight and length growth were demonstrated by the results. feed efficiency, and FCR in white snapper (Lates calcarifer) gave a significantly different effect, while the amount of feed consumption and survival gave an effect that was not significantly different.